On the Integration and Development of Artistic Creativity and Digitalization - Xu Yiyan; Dou Weizhen (SHS Web of Conferences, 2024)
In the era of digital technology, the development of information technology and art culture helps to enhance artistic creativity through digital technology. New forms of art emerge from the parallel between art and "digitization": This article discusses digitization in artistic creativity, and theoretically discusses and summarizes the creativity generated by the integration of artistic ideas and digital art in the current digital era in China. Digitization is a brand new mode of production and economic form, which has become an im-portant standard of modern economic development. At the end of 1980s, the rapid development of digital technology and information technology made digital art appear in the world. Based on computer and Inter-net technology, it has created a space for digital development, and provided a new platform for artists to create digital art in all aspects of digital technology and application ability. At present, digital art is growing into a new art form in the art and creative industry of the 21st century.